Stone/tissue differentiation for Holmium laser lithotripsy using autofluorescence: Clinical proof of concept study. Issue 4 (12th November 2016) - Lange, Birgit; Jocham, Dieter; Brinkmann, Ralf; Cordes, Jens
Abstract : Background and Objectives: Holmium laser lithotripsy is the gold standard for intracorporeal fragmentation of urinary calculi. Usually, a visible beam is superimposed on the IR treatment laser as an aiming beam to guide the surgeon. In vitro tests showed that this aiming beam (532 nm, power <1 mW) excites strong fluorescence on human calculi. Tissue, in contrast, emitted much weaker fluorescence. If this is verified in vivo, the fluorescence signal induced by the aiming beam could be used to implement a feedback loop, preventing the Holmium laser being fired on tissue. Materials and Methods: Fluorescence signals of 67 tissue and 68 stone spots were measured in a clinical proof of concept study with eight patients. For this, a modulated excitation/detection scheme (lock‐in technique) was implemented. A frequency‐doubled, diode‐pumped solid‐state laser module (532 nm, modulation frequency 66 Hz, average power 0.3 mW) was coupled via a dichroic mirror with the Holmium lithotripsy laser into the treatment fiber. The fluorescence signal entering the treatment fiber was detected via another dichroic mirror with a photodiode and a lock‐in amplifier. Results: In most instances (94%), the calculus of a patient gave a signal which was at least twice the maximum signal of ureteral tissue. Conclusion: The results of our proof of concept study indicate that measuring the fluorescence signal of a green aiming beam could be used to implement a feedback loop for Holmium laser lithotripsy. Preventing the laser being fired on tissue, this would increase the safety of the procedure. Lasers Surg. Med. 49:361–365, 2017. © 2016 Wiley Periodicals, Inc.